Hylastes ater (Curculionidae: Scolytinae) Affecting Pinus radiata Seedling Establishment in New Zealand - Stephen D. Reay; Travis R. Glare; Michael Brownbridge (Psyche: A Journal of Entomology)
The introduced pine bark beetle Hylastes ater has been present in New Zealand for around 100 years. The beetle has been a minor pest on pines. Research was undertaken to control the pest in the 1950s–1970s, with a biological control agent introduced with limited success. Following a reasonably long period with minimal research attention, renewed interest in developing a better understanding of the pest status was initiated in the mid to late 1990s. Subsequently, a significant amount of research was undertaken, with a number of studies exploring the role of this pest of exotic forests in New Zealand. These studies ranged from attempting to quantify damage to seedlings, evaluate the role of the beetle in vectoring sapstain fungi, explore options for management, and evaluate the potential for chemical and biological control. From these studies, a number of findings were made that are relevant to the New Zealand exotic forest industry and shed new light onto the role of secondary bark beetles globally.